CITIZENS’ ADOPTION OF AN E-HEALTH SYSTEM DURING THE PANDEMIC - Faye Lorraine Pluma Mina; Enrique Batara; Eucil Hussein; Rabby Lavilles (Jurnal Studi Pemerintahan, 2022)
This study aimed to determine the factors influencing the behavioral intention of PhilHealth members to adopt My PhilHealth Portal using an extended unified theory of acceptance and use of technology (UTAUT). Variables from this theory were operationalized through indicators which were then translated into a self-reported online survey questionnaire distributed through email and Facebook. Purposive-homogeneous sampling was used to determine the sample size from the target population who are Cagayan de Oro City-based PhilHealth formal economy members employed in either private or public sector. Quantitative analysis of data was done using IBM SPSS Statistics (version 20) and IBM SPSS AMOS (version 26). Structural equation modeling was utilized to determine the correlations of variables.Findings show that citizens' behavioral intention to adopt My PhilHealth Portal is influenced by their trust on internet, trust on government, effort expectancy, and their perceived competence. Furthermore, age significantly moderates the effect of effort expectancy, social influence, and facilitating conditions on behavioral intention. Voluntariness of use also appears to moderate the effect of social influence.To increase My PhilHealth portal adoption, PhilHealth must educate its members on the portal's security features and improve staff's ability to implement online services securely. Citizens should have access to a public internet connection as well as knowledge of how to use the portal in order to conduct transactions with ease.